Impact of China-India relationship on the socio-economic factor of Pakistani society - Ali, Aqib (Association for Scientific Computing Electrical and Engineering, 2024)
With the conclusion of the Cold War, India and China both initiated new foreign policies. Financial reciprocity made the improvement of commerce and other energetic and formative endeavors possible. Pakistan, a nation economically dependent on China, is concerned about the growing linkages between these two countries. Enhancing China's connections with India would require shifting China's attention to a more stable and grounded country. This fear was warranted, given that doing so would grant China access to Central Asian governments and improve China's political and economic standing. Pakistan receives support from China in various public and international challenges; nevertheless, having a reliable ally such as India will encourage trade and collaboration in a different area of focus. It has been decided that China will re-evaluate its ties with Pakistan. Despite this, Pakistan has managed to dodge India's clear pull; it will take China some time to adjust its perspective on India if Pakistan's issues of monetary instability, political instability, and security only improve later. Hence, linkages between India and China's monetary system may get more robust, jeopardizing Pakistan's geostrategic and international goals